SMARTPHISH: HYBRID PHISHING WEBSITE DETECTION USING URL AND BEHAVIORAL FEATURES - Mahesh Dixit; Paramjeet Kour; Basavanjali (International Educational Journal of Science and Engineering, 2026)
Phishing attacks remain one of the most prevalent forms of cybercrime, targeting individuals and organizations by impersonating legitimate websites to steal sensitive credentials and financial information. Despite the availability of browser-based blacklists and security warnings, phishing websites continue to evade detection by frequently rotating domains and mimicking trusted platforms. This paper presents Smart Phish, a hybrid phishing detection system that combines URL-based structural features with webpage behavioral indicators to improve detection accuracy using lightweight machine learning models. The proposed system extracts 24 features from two complementary sources: lexical and structural properties of URLs (domain length, use of IP addresses, presence of special characters, HTTPS usage) and webpage behavioral indicators derived from HTML content analysis (redirect patterns, form action attributes, hidden input elements, external link ratios, and suspicious JavaScript constructs). Two classification models, Random Forest and XGBoost, are trained and evaluated on a publicly available benchmark dataset comprising 10,208 phishing and legitimate URLs. Experimental results show that the hybrid feature approach achieves 95.2% classification accuracy using Random Forest, with a false positive rate of 3.8% and ROC-AUC of 0.982. The hybrid approach outperforms URL-only classification by 3.4 percentage points. The system operates with low computational overhead, making it practical for browser extension or lightweight server-side deployment without requiring GPU infrastructure or proprietary threat feeds. Smart Phish provides a reproducible and interpretable approach to phishing detection.